1999
DOI: 10.1128/iai.67.10.5142-5150.1999
|View full text |Cite
|
Sign up to set email alerts
|

Dual Role of Interleukin-10 in Murine Lyme Disease: Regulation of Arthritis Severity and Host Defense

Abstract: In the murine model of Lyme disease, C3H/He mice exhibit severe arthritis while C57BL/6N mice exhibit mild lesions when infected withBorrelia burgdorferi. Joint tissues from these two strains of mice harbor similar concentrations of B. burgdorferi, suggesting that the difference in disease severity reflects differences in the magnitude of the inflammatory response to B. burgdorferi lipoproteins. Stimulation of bone marrow macrophages from C3H/HeN mice with the B. burgdorferi lipoprotein OspA resulted in higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(68 citation statements)
references
References 69 publications
4
63
0
1
Order By: Relevance
“…20 Several studies have shown an association of TNF-a responses with severe symptoms in experimental Borrelia infections, whereas mild disease correlates with lower levels or even lack of TNF-a. [21][22][23] On the other hand, TNF-a secretion, although potentially harmful, may be necessary for eliminating B. burgdorferi, since inability to produce TNF-a was demonstrated in susceptible mice. 24 Previous studies of serum TNF-a in human Lyme borreliosis have shown divergent results, ranging from high 25 to undetectable levels of TNF-a.…”
Section: Discussionmentioning
confidence: 99%
“…20 Several studies have shown an association of TNF-a responses with severe symptoms in experimental Borrelia infections, whereas mild disease correlates with lower levels or even lack of TNF-a. [21][22][23] On the other hand, TNF-a secretion, although potentially harmful, may be necessary for eliminating B. burgdorferi, since inability to produce TNF-a was demonstrated in susceptible mice. 24 Previous studies of serum TNF-a in human Lyme borreliosis have shown divergent results, ranging from high 25 to undetectable levels of TNF-a.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages were isolated using the methods published previously. 30 Briefly, bone marrow from the femur of C57 BL/6 mice was flushed with 10 mL RPMI media containing 10% FBS and 30% L929-conditioned medium (macrophage expansion medium; see below) using a 27 G needle and 5 mL syringe. The cell pellets were dispersed by gently pipetting the suspension using the syringe.…”
Section: Isolation Of Macrophages From Bone Marrow Of Micementioning
confidence: 99%
“…Primary murine macrophages from bone marrow are expanded in vitro either by using L929 supernatants or recombinant macrophages-colony stimulating factor (rM-CSF) or by thioglycolate elicitation from the peritoneum. 30 This study utilized expansion of macrophages from murine bone marrow using L929 supernatants, as this method has been shown to consistently produce high yields of pure macrophage cultures with properties that are similar to those produced using rM-CSF, which is more expensive. 31,32 L929 supernatants were obtained using previously established ORIGINAL ARTICLE JOURNAL OF BIOMEDICAL MATERIALS RESEARCH A | NOV 2013 VOL 101A, ISSUE 11 protocols.…”
Section: Preparation Of L929 Supernatants To Culture Macrophagesmentioning
confidence: 99%
See 2 more Smart Citations